STUDENTS' CONCEPTIONS, TROUBLESOME KNOWLEDGE, AND THRESHOLD CONCEPT OF CATALYST EFFECT ON REACTION RATE - Iqlima Rahayu; Wiji Wiji; Tuszie Widhiyanti; Sri Mulyani (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2022)
Student conceptions provide valuable information for understanding learning difficulties and provide insight into how they can be addressed appropriately. Analyzing students' conceptions can also provide insight into what concepts are troublesome or serve as concepts affecting learning. Using the Interview About Event-Mental Model Diagnostic Test (TDM-IAE), twenty-one high school and university students' conceptions, troublesome knowledge, and threshold concepts for understanding the effect of catalyst to reaction rate were identified. Students mostly held partial mental models or mental models with misconceptions in which three concepts were considered troublesome and threshold concepts for understanding the effect of catalyst on reaction rate.